Sharaf politics : honor and peacemaking in Israeli-Palestinian society - Lang, Sharon D. (Middle East studies (Routledge (Firm)), 2005)
This book examines the Arabic conflict resolution method known as ""sulha."" In this process, notable male elders mediate conflicts between and within Arab communities. A lengthy process of political jockeying culminates in a ceremony that peaks when ""enemies"" shake hands and publicly forgive the crimes of the other. The reality of actual sulha deviates considerably from the ideal, but both the official framework and the actual events point to a deep seated valorization of peace and reconciliation in Israeli-Palestinian society